Seroprevalensi Neospora caninum pada sapi bali yang dipotong di Rumah Potong Hewan (RPH) Denpasar - Adryani Ris; Nyoman Sadra Dharmawan; I Made Damriyasa (Veterinary Science and Medicine Journal, 2014)
Recent years the infection of Neospora caninum parasite has been a significant reproductive disease on cattle. The purpose of this study was to determine the seroprevalence of Neospora caninum in Bali cattle that are slaughtered in Denpasar’s slaughter house.A total of 184 serums was collected and tested using enzyme linked immunosorbent assay (ELISA). The results showed that there were 2 serum samples (1.08%) contain Neospora caninum antibodies. While the remaining samples, 182 samples (98.92%), were negative. Though the neosporosis seroprevalence rate in Bali is very low, a sustainable surveylance must be carried out to mitigate the broadness of the disease distribution.